Partial replacement of meat by superworm (Zophobas morio larvae) in cooked sausages: Effect of heating temperature and insect:Meat ratio on structure and physical stability. (December 2020) - Scholliers, Jana; Steen, Liselot; Fraeye, Ilse
Abstract: The effect of different heating temperatures and different insect:meat ratios on the structural properties and water and fat stabilization of (hybrid) cooked sausages was studied. Structural properties were substantially reduced upon partial replacement of meat by insect, even when only 5 or 10% meat was replaced. Only for sausages with low insect contents (5 or 10% replacement) heated at 90 °C, similar viscoelastic properties compared to a standard cooked sausage could be obtained. However, textural properties remained inferior in all hybrid cooked sausages, even at high heating temperatures. The cooking loss was generally positively affected by the partial replacement of meat by insect, indicating good water and fat stabilization in hybrid cooked sausages during heating and cold storage. However, the hybrid cooked sausages destabilized more easily when subjected to an external force immediately after heating, resulting in an increased fluid release (both water and fat). Industrial relevance: This study provides important insights with regards to the processing and composition of hybrid cooked sausages. Results showed that even the replacement of only 5% meat by insect negatively impacted the structure and physical stability (with the exception of cooking loss) of cooked sausages. Even though applying higher temperatures considerably improved some characteristics (e.g. amount of structure formation and structure stability), the hybrid cooked sausages remained inferior to a standard cooked sausage. Therefore, more research is needed to further improve their structural properties and water and fat stabilization. Highlights: Structure and water and fat stabilization of hybrid cooked sausages was studied. Replacing meat with insect (≥ 5%) negatively affected the structural properties. Generally, cooking loss was positively affected by replacing meat with insect. Increasing the heating temperature improved the structural properties. Overall, all hybrid cooked sausages remained inferior to a standard cooked sausage.